PRESENT AND FUTURE OF SPECIAL EDUCATION - Fayziyeva Ubayda Yunusovna; Abduazizova Shaxzodabonu Abdulnosir qizi (Web of Journals Publishing, 2024)
This article, the opportunities available to children with disabilities in the past, the views on special approaches in the modern era, the research conducted by European and Russian scientists on this topic, the development of special education in Uzbekistan, the current and future stages of development of special pedagogy are described.
Keywords: Special pedagogy, PQ-4860, inclusive education, “Modern school”, hearing impaired children, ramp.